The effect of good corporate governance mechanism on national bank performance - Wardhani, Faradina Inda; Muliani, Muliani (Universitas Muhammadiyah Pontianak, 2018)
The purposes of this research are to provide empirical evidence about (1) mechanisms good corporate governance, and (2) the influence size board of commissioners, size board of directors, and Capital Adequacy Ratio (CAR) toward financial banking performance. Independent variables used the board of commissioner, board of director, and Capital Adequacy Ratio CAR. The sampling in this research by using purposive sampling and obtained 28 companies used samples. The multiple linear regression is an analytical method for study. This research shows the board of commissioner and CAR is not significant to the financial banking performance. The board director is a substantial and positive relationship to the commercial banking performance.